Nine years of phosphorus management with lanthanum modified bentonite (Phoslock) in a eutrophic, shallow swimming lake in Germany. (3rd April 2017) - Epe, Tim Sebastian; Finsterle, Karin; Yasseri, Said
ABSTRACT: Epe TS, Finsterle K, Yasseri S. 2017. Nine years of phosphorus management with lanthanum modified bentonite (Phoslock) in a eutrophic, shallow swimming lake in Germany. Lake Reserve Manage. 33:119–129. Eutrophication is threatening shallow lakes, their functioning and ecosystem services. In recent years, lanthanum modified bentonite (LMB) has been increasingly applied to eutrophic lakes to enforce recovery processes by increasing sediment phosphorus (P)-sorption capacity and reducing P in the water column. In this long-term study, we examined the water quality characteristics of a polymictic, eutrophic swimming lake in central Germany, Lake Bärensee, an artificial, excavated lake suffering from frequent cyanobacterial blooms caused by nutrient enrichment, mostly from swimmers, runoff, and P release from the sediments. Bärensee was first treated with LMB in 2007. This restoration method is based on the strong ionic bond formed between lanthanum (La) and phosphate (PO4 ), which results in the formation of rhabdophane (LaPO4 n H2 O) in the sediment. Smaller reapplications of LMB were conducted in 2010 and 2013 when P concentrations exceeded a defined level as a result of frequent nutrient inputs, primarily by swimmers. The intensity of mineralization processes decreased, preventing large algal and cyanobacterial blooms. Post-treatment chlorophyll a, total nitrogen, and ammonium concentrations indicate that the productivity of the lake has been limited by recurrent small treatments with LMB. Because of this P management, the lake could be used continuously for swimming and recreation.